A Meta-Analysis Of HPV Genotype Distribution In Cervical Intraepithelial Neoplasia And Cancer By Genoflow Method And Comparison Of Other Methods (The Review of Diabetic Studies, 2025)
Background: Persistent infection with carcinogenic high-risk human papillomavirus (HPV) is the main cause of cervical intraepithelial neoplasia (CIN) and cervical cancer. The Genoflow HPV Array has been increasingly employed in clinical and epidemiological studies, but its relative performance compared to other genotyping platforms has not been properly assessed. The aim of this study was to assess the HPV genotype distribution in CIN and cancer by Genoflow method and of other methods.Methods & materials: This meta-analysis was conducted on studies published between 2010 and 2025 that had reported HPV genotype prevalence or diagnostic performance using the Genoflow assay. Study details, comparator tests, genotype-specific prevalence by CIN grade, diagnostic accuracy, pooled estimates of prevalence and measures of concordance were estimated and risk of bias was assessed using acknowledged critical appraisal tools.Result: Ten studies involving over 5,000 cervical samples were included. The most common genotype was HPV-16, increasing from 22% in CIN1 to 65% in cancer (total 45%). HPV-18 accounted for 13% in total, with HPV-52 and HPV-58 contributing significantly in CIN2/3 and cancer. Genoflow was in high concordance with PCR-based assays (89–93%) and Roche Linear Array (88–92%), having 88–92% sensitivity and 87–93% specificity for CIN2+. NGS comparisons were in the highest concordance (93–95%), particularly for low-abundance genotypes.Conclusion: Genoflow is a strong, cost-effective genotyping machine that shows high concordance to reference assays. Though it is less sensitive than NGS, due to its cost and flexibility to self-sample, it is highly useful in low-resource environments.